Diversity of Birds for Ecotourism Attractions in the Mangrove Ecosystem of Nature Conservation Forum Putri Menjangan - GINANTRA, I Ketut; MUKSIN, I Ketut; JONI, Martin (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020, 2020)
Research on bird diversity has been carried out to support ecotourism attractions in the mangrove area of ​​ Conservation Forum Putri Menjangan. The study was conducted in April-July 2018. The focus of this research was identification, description of bird species and habitat use for bird activities. To achieve this goal, the following steps are taken: (1) Identification of bird species based on morphological characteristics, (2) determining the abundance of bird species by point count method (3) determining the activity of birds in each mangrove zoning with the ad libitum sampling method. The diversity of bird species is determined by the Shannon-wiener index. The results of the study found 39 birds species included in 24 families. In each zoning the mangrove forest shows a variety of diversity. The central mangrove zone is showing the diversity of the most diverse species of birds. The birds use mangrove vegetation to perch, forage. Mudflat and tide in mangrove habitats are used by birds for foraging activities. The existence of birds, bird activity, habitat use by birds in mangrove habitat is an interesting attraction in ecotourism.